Professional learning communities and teacher enquiry : evidence-based teaching for enquiring teachers - Fox, Alison; Poultney, Val (Evidence-based teaching for enquiring teachers., 2020)
Written for teachers, this concise guide takes an evidence-based approach to professional learning communities and teacher enquiry, with practical advice on how to engage with and evaluate various models.